A new cycloheptane derivative from the fungus Penicillium crustosum JT-8. Issue 1 (2nd January 2023) - Hu, Jun-Tao; Wang, Jia-Peng; Shu, Yan; Cai, Xue-Yun; Sun, Cheng-Tong; Ding, Hao; Cai, Le; Ding, Zhong-Tao
Abstract: A new highly oxygenated cycloheptane derivative crustane (1 ), along with fourteen known compounds (2 –15 ) were isolated from Penicillium crustosum JT-8. The structure of compound 1 was determined by extensive spectroscopic data, DP4+ probability analyses and dimolybdenum CD method. Compound 1 exhibited moderate antibacterial activity against Staphylococcus aureus with MIC of 4.0 μg/mL. Graphical Abstract: UF0001